2016
DOI: 10.1007/s10068-016-0007-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of nutritional compositions between transgenic rice harboring the CaMsrB2 gene and the conventional counterpart

Abstract: As a part of a safety assessment of new transgenic crops, compositional equivalence studies between transgenic crops with non-transgenic comparators are almost universally required. This study was conducted to compare nutritional profiles of proximate composition, and fatty acid, amino acid, mineral, and vitamin contents, and anti-nutrients, between transgenic drought-tolerant Agb0103 rice harboring the pepper methionine sulfoxide reductase B2 gene and the parental rice cultivar, 'Ilmi' as a non-transgenic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The levels of these anti-nutrients like phytic acid, tannins and trypsin inhibitor in the Bt chickpea event were comparable to their non-transgenic chickpea seeds (Table 1) and were also within the range reported for chickpea varieties (Jukanti et al, 2012). Similar studies were also reported in transgenic pigeon pea (Mishra et al, 2017), rice (Cho et al, 2016) confirming them to be safe.…”
Section: Anti-nutrients Content In Bt Chickpea Seedssupporting
confidence: 79%
See 1 more Smart Citation
“…The levels of these anti-nutrients like phytic acid, tannins and trypsin inhibitor in the Bt chickpea event were comparable to their non-transgenic chickpea seeds (Table 1) and were also within the range reported for chickpea varieties (Jukanti et al, 2012). Similar studies were also reported in transgenic pigeon pea (Mishra et al, 2017), rice (Cho et al, 2016) confirming them to be safe.…”
Section: Anti-nutrients Content In Bt Chickpea Seedssupporting
confidence: 79%
“…A comparative analysis is mostly adopted to evaluate that the transgenic and their non-transgenic counterparts are nutritionally equivalent. Several studies indicated that GM crops are considered safe if their nutritional composition is similar or data are within the range reported for their conventional counterparts (Mishra et al, 2017;Cho et al, 2016;Gayen et al, 2013;Junhua et al, 2005;Oberdoerfer et al, 2005;Wang et al, 2012). Therefore, we assessed the key composition determining seed protein quality of chickpea and compared the data with the nontransgenic parent (Jukanti et al, 2012), USDA, (2018).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, AcoDREB16 and its homolog in rice (LOC_Os10g22600) are both highly expressed in roots. OsDREB2A, when overexpressed in rice, enhances salt stress tolerance (Mallikarjuna et al, 2011), without changing its total nutritional composition (Cornwell, 2014;Cho et al, 2016). Our analysis suggested that overexpression of some AcoDREBs in pineapple could help to develop new pineapple varieties with abiotic stress tolerance.…”
Section: Discussionmentioning
confidence: 82%
“…Mycotoxins, such as gibberellin and fumonisins, produced by F. f ujikuroi, not only affected the quality of rice but also did great harm to human and animal health. 5,6 Due to the production of gibberellin, the infected seedlings were slenderer than healthy seedlings, and the leaf sheaths were elongated abnormally. 7 Fungicide treatment of infected seeds is one of the most effective measures to control RBD.…”
Section: Introductionmentioning
confidence: 99%